Quality and safety continuous improvement through lean tools - Santos, Gilberto (2019)
The purpose of this chapter is to suggest the use of several lean tools that can be used, indicating the improvements that can be obtained with each of the recommended tools. The main objective is to be a contribution to the organizations, showing how they can detect the wastes in the productive flow through VSM, and at the same time to improve the quality of products through lean tools. The method presented was a case study. The various lean tools were also collected and described. This chapter intends to show several lean tools that can be applied in different situations, as well as, the wastes that each can eliminate and the benefits that are obtained from each one. Throughout the production process, with the support of Value Stream Mapping (VSM), it was possible to detect several wastes. A case study is presented as results from a work carried out in a company that is dedicated to the production of mechanical equipment. This work can be a guide to support organizations that wish to start their lean road. Smart value creation remains today dependent on the maturity of how lean management tools are applied. Lean, innovative technologies, critical knowledge, talent and big data need other dimensions to be sustainable. Quality and safety continuous improvement through lean tools, as well as, Industry 4.0 assumes a critical pillar for the new journey toward the future of our organizations.